Effect of biochar and cyanobacteria crust incorporation on soil wind erosion in arid mining area under freeze-thaw action - Zhe Wang; Xueshi Liu; Fenghui Sun; Qinghong Jiang; Haili Shang; Chunli Zheng (Scientific Reports)
Abstract The Bayan Obo mining areas of northern China’s arid regions is prone to wind erosion and strong freeze-thaw effects. Freezing-thawing leads to the degradation of soil structure and diminishes its resistance to wind erosion. Cyanobacteria crusts can inhibit wind erosion, but their biomass decreases under freeze-thaw conditions. There is limited research on whether combining biochar with cyanobacteria crusts can alleviate the impact of freeze-thaw on their wind erosion resistance. Therefore, the indoor simulated freeze-thaw and wind tunnel tests were used to systematically investigate the impact of cyanobacteria crust and biochar combination on soil wind erosion under freeze-thaw action. Results showed that freeze-thaw cycles altered crust layer soil physicochemical properties. The Pearson correlation coefficient revealed that the freeze-thaw frequency exhibited a significant negative correlation with pH (p < 0.01), bulk density (p < 0.01), clay percentage (p < 0.01), and > 0.25 mm aggregate content (p < 0.05). The sensitivity of freeze-thaw cycles to clay percentage was the highest, with a coefficient of variation of 27%. The wind tunnel test showed that the combined use of biochar and cyanobacteria exhibited the most efficient erosion reduction, the erosion reduction rate peaked at a wind speed of 15 m/s, reaching an impressive 64.73%. This was primarily attributed to the high aggregate stability and clay percentage. The above results indicate the biochar and cyanobacteria crust incorporation has great potential as a wind erosion control strategy in seasonal freeze-thaw zones.